The unfolding of language : the evolution of mankind's greatest invention - Deutscher, Guy, Dr (Arrow, 2006)
""Language is mankind's greatest invention - except of course, that it was never invented." So begins linguist Guy Deutscher's investigation into the evolution of language. No one believes that the Roman Senate sat down one day to design the complex system that is Latin grammar, and few believe, these days, in the literal truth of the story of the Tower of Babel. But then how did there come to be so many languages, and of such elaborate design? If we started off with rudimentary utterances on the level of "man throw spear," how did we end up with sophisticated grammars, enormous vocabularies, and intricately nuanced shades of meaning?".